O design de interiores como instrumento de melhorias na prestação de serviços aos usuários da Biblioteca Central da UFPA - MARTINS, Camilla dos Santos (2018)
Stresses the importance of Interior Design in libraries as a means to more efficiently serve users. It seeks to identify, through a case study at the UFPA Central Library, the users' satisfaction with the layout of the spaces and internal environmental factors of this information unit, especially on the hall, reference and reading room. Perform through a bibliographical research, the theoretical basis in the themes about architecture and interior design and planning of information unit, and through a descriptive research with a quantitative approach, which aimed to know the evaluations by environment and by environmental factors, such research was carried out using a structured questionnaire applied to students in the library. The final result of the research was presented in quantitative charts elaborated in Excel, which made it possible to understand that the lack of balance of environmental factors with the specific internal areas results in a considerable dissatisfaction with these areas of the library.